Meningkatkan Hasil Belajar Siswa Dengan Metode PBL Kelas VI SDN 013 Balikpapan Materi Gereja Persekutuan Para Kudus - Bartolomeus Na Helan; Ansel Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study addresses the low level of student understanding in the Catholic Religious Education and Character subject (PAKBP) at SDN 013 Balikpapan Kota, as evidenced by learning evaluation results that did not meet the Minimum Mastery Criteria of Learning Objectives (KKTP). The lack of interactive learning models has limited student engagement, prompting the researcher to implement the Problem-Based Learning (PBL) method, which emphasizes active problem-solving. The research focused on sixth-grade students and explored whether PBL could improve learning outcomes, particularly on the topic of the Church as the Communion of Saints. This Classroom Action Research (CAR) was carried out in two cycles, each consisting of planning, implementation, observation, and reflection phases. The subjects were six sixth-grade students. Findings revealed significant improvements following the PBL implementation. In the first cycle, 83.3% of students achieved the “competent” category, while 16.7% were in the “proficient” category. Participation levels included 16.67% in “developing,” 50% in “competent,” and 33.33% in “proficient.” By the second cycle, student outcomes improved, with 66.7% reaching the “proficient” level and 33.3% attaining “advanced.” Active participation also rose, with 66.67% in “proficient” and 33.33% in “advanced.” These results demonstrate that the PBL method is effective in enhancing both learning outcomes and student engagement in Catholic Religious Education, especially in fostering deeper understanding of core religious concepts.